1979
DOI: 10.1002/chin.197902172
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: 1,5‐DIAZABICYCLO(3.3.0)OCTADIENEDIONES (9,10‐DIOXABIMANES). STRONGLY FLUORESCENT SYN ISOMERS

Abstract: Aus 4‐Chlor‐pyrazolonen‐(5) (I) entstehen unter der Einwirkung von Basen wie K2CO3 bei Raumtemp. syn‐ (II) und anti‐Isomere (III) der Titelverbindungen; unsymm. Verbindungen dieses Typs erhält man z.B. ausgehend von äquimolaren (Ia)‐(Ib)‐Gemischen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…1 Some examples include anti-Alzheimer’s disease molecule 1 and related bicyclic pyrazolidinone derivatives that exhibit herbicidal, pesticidal, and antibiotic activity (Scheme 1). 1 However, the catalytic asymmetric synthesis of pyrazolidinones of structure 1 has proven an elusive target.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Some examples include anti-Alzheimer’s disease molecule 1 and related bicyclic pyrazolidinone derivatives that exhibit herbicidal, pesticidal, and antibiotic activity (Scheme 1). 1 However, the catalytic asymmetric synthesis of pyrazolidinones of structure 1 has proven an elusive target.…”
mentioning
confidence: 99%
“…1 Some examples include anti-Alzheimer’s disease molecule 1 and related bicyclic pyrazolidinone derivatives that exhibit herbicidal, pesticidal, and antibiotic activity (Scheme 1). 1 However, the catalytic asymmetric synthesis of pyrazolidinones of structure 1 has proven an elusive target. 2 Enantioselective access to pyrazolidinone motifs could be envisaged through a chiral catalyst-controlled 1,3-dipolar cycloaddition of an azomethine imine with a suitable dipolarophile reactant partner.…”
mentioning
confidence: 99%
“…[8][9][10] As a potential scaffold for such amyloid dyes, bimane is a highly attractive structure to its small size and relatively low toxicity. [11][12][13][14][15][16][17] Bimane was introduced by Kosower and coworkers nearly four decades ago, 13,14 , and is widely used for in vitro protein labeling as cysteine-reactive monobromobimane (Scheme 1, 2). 12,[15][16][17] However, there have been some applications in cells, and it has been shown that a syn-bimane adduct of a-aminobutyric acid can cross the blood-brain barrier in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Tetrahydropyrazolopyrazolones have been investigated as antibacterial agents, 16 herbicides, pesticides, 20 antitumor agents, 21 calcitonin agonists, 22 and potent drugs to relieve Alzheimer’s disease. 23 Pyrazolopyridazinone derivatives have been studied extensively as pesticides and, especially, herbicides; more than 60 patents have been filed according to the CAS database. Pyrazolodiazepinone and pyrazolodiazocinone derivatives have also been explored as herbicides, insecticides, acaricides, 24 and acetyl-CoA carboxylase inhibitors.…”
Section: Introductionmentioning
confidence: 99%